Environmental variables influencing regeneration of Nothofagus pumilio in a system with combined aggregated and dispersed retention - Martínez Pastur, Guillermo José (2011)
The current silvicultural prescriptions for Nothofagus are designed to stimulate natural regeneration by opening the canopy. One of these methods is variable retention, which can include either or both aggregated and dispersed retention. Different degrees of retention may modify microclimatic variables differently and consequently offer dissimilar microenvironmental conditions for regeneration. Retained canopy influences both biotic and abiotic factors. The objective was to evaluate Nothofagus pumilio regeneration along edge-related gradients within aggregated retention, and in the different microenvironments within the harvested areas. The remnant canopy cover after harvesting greatly influenced regeneration mainly by decreasing radiation transmittance and soil moisture availability. Aspect (direction to the azimuth) and distance from edge of aggregates influenced regeneration density, height and growth. In dispersed retention, microenvironments generated by different types of understory plant cover, debris, and proximity of remnant trees also influenced regeneration. High levels of understory cover (up 50%) and medium levels of harvesting debris cover (25–50%) had a positive impact, while close proximity to remnant trees had a negative impact on regeneration. These findings can be used to improve silvicultural and harvesting prescriptions to ensure successful establishment of regeneration and maximize potential growth.